Performance Analysis of Photovoltaic Module with Different Passive Cooling Methods - Azahari M.A.B.; Long C.Y.; Yan K.Y. (IOP Publishing Ltd, 2023)
This paper analyses the difference in terms of performance of passive cooling systems for photovoltaic (PV) modules. The objective of this paper is to identify which passive cooling systems offers the best results in reducing the operating temperature and improving the generation of output power. The performance of photovoltaic (PV) module will gradually decrease as the operating temperature increases. The energy from the sun's photons are not enough to knock out the electrons from the atom to generate more electricity. That being the case, two passive cooling systems is developed which is the cotton wick structures with water and aluminium fins were attached to the back side of the photovoltaic (PV) module. The cotton wick structures with water utilises the capillary action of the water to extract excess heat from the module while the aluminium fins act as a heat sink that can remove heat from module to the adjacent air. Results showed that the cooling systems managed to enhance the output power by an average of 3.94% for the module with cotton wick structures with water while an average of 2.67% increment for the module under aluminium fin mounted as the cooling system. Published under licence by IOP Publishing Ltd.